Clark H. Pinnock, Flame of Love: A Theology of the Holy Spirit. Downers Grove: Intervarsity Press, 1996. 280 pp. - Gani Wiyono (Jurnal Teologi Amreta (ISSN: 2599-3100))
Flame of Love is written by Clark Pinnock of McMaster Divinity College, one of the most evangelical stimulating theologians today. It is basically a one-volume systematic theology with the Spirit as its central motif. Chapter one discusses the Spirit and the Trinity. Here, Pinnock develops a relational (or social) model of God which views Godhead as a community of love and mutuality.